Muertes por incidentes viales en Bello (Antioquia) (2012-2016) (2019)
ABSTRACT: To determine the structure of mortality due to road incidents in the municipality of Bello (Antioquia), from 2012 to 2016. Methodology: Descriptive study with information obtained from the databases about deaths, the automotive fleet, as well as the road network in the municipality. Mortality rates for relevant variables were calculated. Also, the profile of a deceased person was determined via multiple correspondence analysis. Furthermore, the spatial distribution of deaths was found through a Kernel density estimation map according to the quantile standard classification method. Results: 313 deaths caused by road incidents were registered. 63 per year on average (being 13.4 per 100,000 inhabitants). This reality was specifically observed in men (62 vs. 12 women per 100,000), who were 19 to 28 years old (47.9 %), had primary school education (32.5 %), and did not have insurance (44 %). Most road incidents were crashes (53 %) and run-overs (41 %), on weekends and from 0:00 to 6:00 a.m. (29.2 %). Motorcycles caused the most fatal road incidents (74.4 %). The routes with the highest concentration of fatalities were: a segment of the Autopista Norte —between diagonales 50 and 52 (14 %), Calle 46 (2.2 %) and Carrera 50 (5.1 %)— Avenida Medellín-Bogotá (5.1 %), and in the Suárez and Niquía areas (2.37 and 1.78 per 100,000 inhabitants). Conclusions: Given the significant increase of road incidents —and therefore deaths linked to it— the effectiveness of interventions performed so far is brought into question and a reassessment of those interventions is suggested.